Exploring Writing Anxiety of the EFL University Students in Pontianak Indonesia - Aunurrahman Aunurrahman (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2019)
The purpose of the descriptive study is to explore the English as a foreign language second-semester students’ writing anxiety. The students were from a private university in Pontianak, West Kalimantan, Indonesia. A total of 92 students who were selected randomly filled the writing anxiety questionnaire. The writing anxiety questionnaire reports that 53.26 % (n= 49) of the students experienced low writing anxiety and 46.74% (n= 43) of the students experienced high writing anxiety. In terms of the components of writing anxiety, the students experienced anxiety in the component of evaluation (mean score of 19.86), product (mean score of 19.25), and stress (mean score of 16.52). This study also has shown that writing anxiety caused by stress can be considered less frequent anxiety component that has been experienced by the students. It is suggested that students should learn to manage their problems that are related to writing. To do so, the lecturer should guide the students to help them to reduce their writing anxiety and help improve the students’ writing skills.